A STUDY OF THE SYNTHESIS OF VERATRYL CYANIDE REQUIRED AS AN INTERMEDIATE FOR THE PREPARATION OF C-9154 ANTIBIOTIC DERIVATIVE FROM VANILIN - Ila Rosilawati; Jumina Jumina; M Muchalal (Universitas Gadjah Mada, 2002)
The synthesis of veratryl cyanide [1-(3,4-dimethoxy phenyl acetonitril] required as an intermediate for the preparation of C-9154 antibiotic derivative was carried out. The starting material used was vanilin, while the reaction steps consisted of (1) methylation of vanilin, (2) reduction of veratraldehyde, (3) synthesis of veratryl bromide, and (4) treatment of this bromide with KCN. The analysis of the products was carried out using IR, 1H NMR and GC-MS spectrophotometers. The methylation of vanilin was conducted using dimethylsulfate and NaOH at 100 oC for 2 hours to give 79.3% yield of veratraldehyde. The reduction of veratraldehyde with LiBH4 in ethanol - THF mixture (1:1 v/v) at reflux for 4 hours afforded veratryl alcohol in 85.3% yield. This veratryl alcohol was treated with red phosphorous and Br2 in CCl4 at 60 oC for 2 hours to give 1-(2-bromo-4,5-dimethoxy)-phenyl bromomethane in 67.4% yield, instead of the desired veratryl bromide [1-3,4-dimethoxy)-phenyl bromomethane]. This benzyl bromide derivative was then treated with KCN in the presence of tween 80 as a phase catalyst transsfer in benzene-water solvent system at reflux for 2 hours to yield 1-(2-bromo-4,5-dimethoxy)phenyl acetonitril in 58.5%.